(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Farid M, Anshori MF, Ridwan I. 2022. Tomato F3 lines development and its selection index based on narrow-sense heritability and factor analysis. Biodiversitas 23: 5790-5797. The F3 is the early selection generation that has a good heritability and heredity pattern in a segregated population. The aims of this study are to identify the effectiveness of forming a selection index based on narrow-sense heritability and factor analysis and to select potential tomato F3 lines to be continued in the F4 generation. The research was arranged by an augmented design combined with a randomized complete block design as the environmental design. The research factors consisted of non-repeated genotypes, i.e. the lines with a limited number of seeds consisting of 75 lines and repeated genotypes as comparison varieties consisting of three varieties (Mawar, Tymoty, and Karina). The lines that were not repeated were divided into 5 blocks, while the check varieties were planted repeatedly in each block. The effective selection criteria in this study were the yield, fruit weight, number of branches, and total fruit number. The priority character besides yield in this study is fruit weight with high and normal narrow-sense heritability. The index selection results from this study showed that there were a good 32 tomato lines to be continued in the F4 generation. t was considered effective in the selection of tomato lines of the F3 generation.